anonymous
  • anonymous
|7-3b|= |5b+15|
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Use the definition of absolute value; that is, the absolute value of a quantity, y, is defined by,\[|y|=\sqrt{y^2}\]So, for your problem, we have,\[\sqrt{(7-3b)^2}=\sqrt{(5b-15)^2}\]You can then square both sides to get\[(7-3b)^2=(5b-15)^2\]Expand and collect your terms into a quadratic equation\[16b^2-108b+176=0\]and solve for b:\[b=4, \frac{11}{4}\]
anonymous
  • anonymous
i am trying to find the possible values for the inequality in this problem.....i didnt think it was a quadratic equation.
anonymous
  • anonymous
You posted an equality...

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
The solutions are b = -1 and b = -11. Lokisan put 5b - 15 instead 5b + 15 which led to incorrect answers. I did it by breaking the absolute value into separate equations. I'll do it this way: |7 - 3b| = |5b + 15| --> 7 - 3b = |5b + 15| OR 7 - 3b = -|5b + 15|. Equation A: 7 - 3b = |5b + 15| 5b + 15 = 7 - 3b --> 8b = -8 --> b = -1 5b + 15 = -(7 - 3b) = 3b - 7 --> 2b = -22 --> b = -11 Equation B: 7 - 3b = -|5b + 15| OR 3b - 7 = |5b + 15| 5b + 15 = 3b - 7 --> 2b = -22 --> b = -11 5b + 15 = 7 - 3b --> 8b = -8 --> b = -1
anonymous
  • anonymous
Yeah, my bad.
anonymous
  • anonymous
oh wow....thats a long problem lol but i will try it, thank you both
anonymous
  • anonymous
and i was also thinking I had to set them both to zero because I had an example that looked the same that did that
anonymous
  • anonymous
It's best to use either the definition of absolute value (like I did) or branlegr's case method.

Looking for something else?

Not the answer you are looking for? Search for more explanations.